The role of security in the presence of children in public spaces of Shandiz City - Daneshvar Anbaran, Fatemeh (2021)
Today, the urban environment is not only a space for daily living, but also should be a safe environment for the growth and excellence of the talents of citizens, especially children. Because children, as one of the most vulnerable groups, need safe spaces for their activities, this platform should be provided with proper planning by urban planners, geographers and thinkers of other sciences. The purpose of this study is to search for physical and social criteria in urban spaces in order to investigate the role of security in the presence of children in public spaces of the small town of Shandiz to increase the sense of security in these environments. This research is of applied type and its method is descriptive-analytical and the parametric statistical methods of Spearman correlation coefficient have been used to measure and analyze 370 citizen questionnaires designed according to Likert format using SPSS software. The statistical society of this study is 0-14 year old children in Shandiz. The results of this study show that the correlation coefficient for the two factors of safety and security are equal to 0.21 and 0.24 and positive, respectively, so the two factors of safety and security are directly related to the presence of children, and so the presence of children in public spaces of Shandiz city is affected by safety and security factors, which according to the citizens of Shandiz, public spaces in this city have a low and very low safety and security index.